ANALISIS TINGKAT KETIMPANGAN PENDAPATAN REGIONAL DI PULAU LOMBOK TAHUN 2019-2020 - Muhammad Maliki; Laili Hurriati (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2022)
This study aims to determine how big the level of regional income inequality between districts/cities on Lombok Island in 2019–2020. This type of research is quantitative using a descriptive approach. The data used in this study is secondary data sourced from data published by the Central Statistics Agency in the form of (1) per capita income data for each district/city on the island of Lombok (2) population data for each Regency/city on the island of Lombok. Analysis of the data used is using the Williamson index analysis. From the results of data analysis using the Williamson index, it shows that the level of regional income inequality in 2019 was 0.56, while in 2020 it was 0.58.